Bearing the Burden of Tick-Borne Encephalitis in Europe, 2012-2020: Rising Cases, Future Predictions and Climate Change - Varma, Aswathy; Szlaszynska, Marta; Ben-Haim, Assaf; Ilia, Neofytos; Tarricone, Silvia; Lewandowska-Bejm, Justyna; Visentin, Francesco; Gadler, Annalisa (International Journal of Medical Students, 2022)
Background: Tick-borne encephalitis (TBE) is a central nervous system disease that is posing a growing public health challenge in Europe. Its disease burden, despite carrying a significant global impact, is still relatively unexplored. This study aims to outline a regression model of how the increasing cases will influence the burden of TBE in the upcoming years, using YLDs (years lived with disability) and DALYs (Disability-adjusted life years), and address climate change as a determinant. Methods: Information regarding the number of cases, YLDs and DALYs of TBE was collected from European countries using available surveillance data from 2012 to 2020. Number of TBE cases and burden projections were created until 2025, using a linear regression model. The total reported cases of TBE cases in this timeframe, age-group and gender distribution were inserted and modeled in ECDC BCoDE Toolkit, a software application that calculates the burden of communicable diseases, YLDs and DALYs of each year. A non-systematic bibliographic search was conducted exploring the impact of climate change on TBE. Results: Our findings showed a linear growth in number of TBE cases (74.3% increase), DALYs (71.3%), YLDs (71.75%) in European countries from 2012 to 2020. By 2025, these factors are likely to increase by 141% (95% CI: [108%,175%]), 134% (95% CI: [91%,177%]) and 134% (95% CI: [98%,172%]) compared to 2012, respectively (p<0.0001). Conclusions: The likelihood of morbidity and mortality increase of TBE, as well as climate-related changes in tick activity, highlight that prompt action is necessary by introducing preventive measures in European populations.